2022
DOI: 10.1186/s12887-022-03162-z
|View full text |Cite
|
Sign up to set email alerts
|

Pattern, frequency and causes of dental extraction among children/adolescents Syrian refugees: an observational study

Abstract: Background The Syrian conflict has had a massive impact on the dental health of refugees. Dental extraction is a good indicator of socioeconomic position and degree of oral hygiene, however there is a scarcity of evidence in the scientific literature that characterizes the reasons for extraction in refugees. Aims and methods The current study looked at the extraction causes and related sociodemographic variables of 322 Syrian refugees (46.3% female… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…These results were similar to prior studies which is that the most common reason for having to take out primary teeth is also because there are dental roots in the mouth. [19][20][21] According to the findings of this study, exfoliated teeth are also one of the leading causes of tooth extraction. It may be the result of protracted tooth movement or physiological changes.…”
Section: Discussionmentioning
confidence: 78%
“…These results were similar to prior studies which is that the most common reason for having to take out primary teeth is also because there are dental roots in the mouth. [19][20][21] According to the findings of this study, exfoliated teeth are also one of the leading causes of tooth extraction. It may be the result of protracted tooth movement or physiological changes.…”
Section: Discussionmentioning
confidence: 78%
“…To eliminate this variable, only one dentin disc obtained from one primary tooth was used to perform the experiments. Moreover, a primary lower second molar was chosen to obtain the dentin disc, in light of previous studies that have indicated that the lower second molar is the most vulnerable primary tooth to be affected by caries [31]. The thickness of the resin composite selected was 2 mm to be clinically practical [32].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a primary lower second molar was chosen to obtain the dentin disc, in light of previous studies that have indicated that the lower second molar is the most vulnerable primary tooth to be affected by caries. 31 The thickness of the resin composite selected was 2 mm to be clinically practical. 32 Additionally, a one microhybrid resin composite with shade A3 was used to eliminate any possible variation in thermal conductivity.…”
Section: Discussionmentioning
confidence: 99%